Fare Design in Urban Transit Network considering Elastic Demand and Adverse Weather's Impact. (15th April 2014) - Zhang, Jiantong; Lv, Biyu; Tian, Guichao; Liu, Wenchi
Abstract : Due to the disturbance of unexpected effects and adverse weather conditions, transit supply and demand manifests many uncertainties. In this paper, we take account of these uncertainties and propose a transit fare structure design model including both ground and underground public transportation. Such transit fare design problem is described through bilevel programming, in which the upper level is the transportation authority's transit fare structure decision aiming to minimize the transit network's total travel and operation cost, while the lower level is a transit network assignment model considering supply and demand uncertainties that influence passengers' travel choice decisions. A heuristic algorithm is developed to solve the problem, and a numerical example is presented to illustrate the application. We get some important results: (1) a diversified fare structure considering uncertain weather's impact is quite necessary; (2) when the value of time is at a high level, metro fare should be higher than bus fare; (3) the optimal metro and bus fare should be close under an extremely adverse weather condition; (4) fare structure could be quite different with varied value of time.